MiR-130a-3p Alleviates Liver Fibrosis by Suppressing HSCs Activation and Skewing Macrophage to Ly6Clo Phenotype - Liu, Lei; Wang, Peng; Wang, Yun-Sheng; Zhang, Ya-Nan; Li, Chen; Yang, Zi-Yin; Liu, Zi-Hao; Zhan, Ting-Zheng; Xu, Jing; Xia, Chao-Ming (Frontiers in Immunology, 2021)
Emerging evidences have highlighted the crucial role of microRNAs (miRNAs) in the liver cirrhosis, but the relationship between miR-130a-3p and liver cirrhosis is not entirely clear. As we all known, schistosomiasis, as one of zoonoses, can lead to liver cirrhosis in advanced schistosomiasis. In this study, we investigated the biological functions of miR-130a-3p on liver fibrosis of schistosomiasis in vivo and in vitro. The mice infected with Schistosoma japonicum (S. japonicum) were treated with lentivirus vector (LV)-miR-130a-3p by hydrodynamic injection through the tail vein. Our findings showed significantly decreased expression of miR-130a-3p both in the serum of patients with cirrhosis and in the liver of mice infected with S. japonicum. The results showed that LV-miR-130a-3p could effectively enter into the liver and alleviate liver granulomatous inflammation and collagen deposition. Simultaneously, LV-miR-130a-3p promote macrophages presented Ly6Clo phenotype, concomitant with the decreased expression of tissue inhibitor of metalloproteinases (TIMP) 1, and increased expression of matrix metalloproteinase (MMP) 2, which contribute to the dissolution of collagen. Furthermore, overexpression of miR-130a-3p not only inhibited the activation and proliferation of hepatic stellate cells (HSCs), but also induced the apoptosis of HSCs. In addition, we also confirmed that miR-130a-3p enables to bind with mitogen-activated protein kinase (MAPK) 1, transforming growth factor-beta receptors (TGFBR) 1 and TGFBR2 genes and inhibit the expressions of these genes. Our findings suggested that miR-130a-3p might represent as the potential candidate biomarker and therapeutic target for the prognosis identification and treatment of schistosomiasis liver fibrosis.